Results in the valuation of some balcony plants Hungary - Fekete, Sz.; Tilly Mándy, A. (International Journal of Horticultural Science, 2005)
Three varieties of different species of annual bedding and balcony plants were examined in balcony boxes in three different places (Budapest, Solymár-Kerekhegy, Tázlár) in order to determine their tolerance to different climate conditions. The experiment proved that Celosia argentea L. var. plumosa 'Savaria' and Dichondra repens J. R. Forst. et G. Forst 'Silver Falls' tolerate well the Hungarian extremely dry, hot and changing climate. Nemesia Vent. 'Blue Bird' developed and flowered well only in cooler and protected conditions; therefore, this species can be offered to a more balanced climate as the western areas of Hungary and the mountains.